2015
DOI: 10.1007/s11738-015-1899-3
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid alleviates the heat stress-induced oxidative damage of starch biosynthesis pathway by modulating the expression of heat-stable genes and proteins in wheat (Triticum aestivum)

Abstract: High temperature reduces the growth and yield of most of the agriculturally important crops. Elicitors have been reported to modulate the thermotolerance of crops under abiotic stresses. Here, we studied the effect of salicylic acid (SA) on thermotolerance level of C306 (thermotolerant) and PBW343 (thermosusceptible) wheat cultivars grown under heat stress. Pilot experiment confirmed spraying of 100 mM SA prior to heat stress (38°C, 2 h) as the most effective treatment. Numerous protein spots were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Additionally, our previous results indicated that 0.1 mM SA sprayed on rice plants at the floret differentiation stage noticeably alleviated the inhibition on the spikelet numbers caused by heat stress; however, no significant differences were found among SA treatments between 0.1–10 mM [ 3 ]. This phenomenon was also described by Kumar et al [ 60 ], who suggested spraying of SA at 100 mM prior to heat stress as a most effective treatment in wheat cultivars that face heat stress. However, when we added SA to the nutrient solution, the rice plants were severely inhibited at higher concentrations compared to control conditions.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, our previous results indicated that 0.1 mM SA sprayed on rice plants at the floret differentiation stage noticeably alleviated the inhibition on the spikelet numbers caused by heat stress; however, no significant differences were found among SA treatments between 0.1–10 mM [ 3 ]. This phenomenon was also described by Kumar et al [ 60 ], who suggested spraying of SA at 100 mM prior to heat stress as a most effective treatment in wheat cultivars that face heat stress. However, when we added SA to the nutrient solution, the rice plants were severely inhibited at higher concentrations compared to control conditions.…”
Section: Discussionsupporting
confidence: 60%
“…High temperature (30 C) resulted in a significant reduction in FW and soluble starch synthase activity of T. aestivum [46]. Foliar application of SA improved the FW, total RNA, and soluble starch synthase activity.…”
Section: Extreme Temperaturesmentioning
confidence: 98%
“…The role of SA in mitigating abiotic stress has widely been studied since last few decades ( Tables 1-4). A large volume of research reports indicate that both endogenous SA synthesis and exogenous application enhance plants tolerance to salinity [38][39][40][41][42], drought [43][44][45], extreme temperature [46][47][48][49], toxic metal and metalloids [50][51][52][53], and others [54][55][56][57][58]. Exogenous SA showed enhanced plant growth, photosynthesis, and decreased ROS production under various abiotic stresses (Tables 1-4 and Figure 2).…”
Section: Salicylic Acid and Abiotic Stress Tolerancementioning
confidence: 99%
“…The results suggested that SA supplementation alleviates heat stress effects by interacting with proline metabolism and ethylene formation to improve photosynthesis in wheat plants. In yet another related work, Kumar et al [60] by using MALDI-TOF-TOF/MS analysis showed that spraying 100 mM SA alleviates the heat-induced (38°C) oxidative stress damage in wheat plants via modulation of the expression of heat-stable genes and proteins. Thus, SA application plays a pivotal role in alleviation the damages of myriads of abiotic stress in diverse crop plants.…”
Section: Role Of Salicylic Acidmentioning
confidence: 99%